ANALISA KINERJA SIMPANG TAK BERSINYAL (STUDI KASUS: SIMPANG TIGA JL. WILLIAM ISKANDAR PASAR V) (JURNAL ILMIAH MAKSITEK, 2023)
The problem that researchers examine here is "How to evaluate the traffic performance of unsignalized intersections on Jl. William Iskandar-Jl. William Iskandar Pasar V?”. The object of the research is the intersection of Jl. William Iskandar-Jl. William Iskandar Pasar V. Determining objects based on observations made by researchers of local residents. The performance of roads in the Medan area has several problems, one of which is congestion and queues at various intersections, both unsignaled and signalized, such as at the unsignalized intersection Jl. William Iskandar and Jl. William Iskandar Pasar V which is in Medan Tembung District. So that the degree of saturation, capacity level, and side obstacles that appear on the Jl. William Iskandar and Jl. William Iskandar Pasar V could be found, so the researcher used the MKJI method (Indonesian Road Capacity Manual 1997) to analyze all the data that the researcher had collected in the form of vehicle volume at peak hours. The results stated that the causes of traffic jams were the large number of public transport that dropped off passengers haphazardly, the phenomenon of illegal or haphazard parking, and the presence of markets or shops at road intersections. After going through various calculations, researchers found that the road had 0.22 degrees of saturation, 4946 pcu/hour road capacity, 95.2 pcu/hour side obstacles, and 1630 pcu/hour traffic volume.